Rastropsha (slyibum marianum) in Surkhandarya soil climatic conditions growth, development and medicinal properties (Texas Journal of Agriculture and Biological Sciences, 2023)
The botanical description, chemical composition, pharmacological properties, folk medicine significance of the plant Rastropsha have been studied.